A Phosphorus Analogue of p‐Quinodimethane with a Planar P4 Ring: A Metal‐Free Diphosphorus Source. Issue 13 (4th February 2019) - Rottschäfer, Dennis; Neumann, Beate; Stammler, Hans‐Georg; Kishi, Ryohei; Nakano, Masayoshi; Ghadwal, Rajendra S.
Abstract: Para ‐quinodimethane ( p QDM) is a fundamental structural component in many π‐conjugated organic molecules and materials. The incorporation of phosphorus atom into π‐conjugated frameworks offers unique opportunities for controlling the properties of derived species. A phosphorus analogue of p ‐quinodimethane ( p QDM), (IPrC)2 P4 [5, IPr=CN(Ar)CH2 2 ; Ar=2, 6‐ i Pr2 C6 H3 ] featuring a planar P4 ring, was readily accessible by KC8 ‐reduction of (IPrC)(PCl2 )2 (2 ). Base‐mediated C−H functionalization of IPrCH2 (1 ) with PCl3 afforded2 . The formation of5 was expected to occur through a dimerization of the transient 3H‐diphosphirene (IPrC)P2 (4 ), which was theoretically suggested to have an intermediate diradical character. Compound5 underwent photo‐induced ring‐contraction reaction to form the singlet diradicaloid (IPrCP)2 VI and white phosphorus (P4 ). The formation of andVI and P4 suggested the formal diphosphorus (P2 ) elimination from5 . Indeed, photolysis of a mixture of 1, 3‐cyclohexadiene (CHD) and5 led to the formation of P2 ‐entrapped product (CHD)2 P2 (6 ). The compound5 represents the first organophosphorus species that functions as a P2 source. Abstract : Metal‐free P2 transfer : A phosphorus analogue of p ‐quinodimethane [(IPrC)2 P4 ] (5, IPr=1, 3‐Bis(2, 6‐diisopropylphenyl)imidazol‐2‐ylidene), was readily accessible through KC8 ‐reduction of (IPrC)(PCl2 )2 (2 ). The P4 ring of5 is perfectly planar and embedded with trans ‐apical N‐heterocyclic vinylidene ligands. Compound5 served as a metal‐free diphosphorus (P2 ) source, which was captured with 1, 3‐cyclohexadiene (CHD), giving P2 (CHD)2 (6 ).